Characteristics and Outcomes of Patients with Bicycle-Related Injuries at a Regional Trauma Center in Korea - Yoonhyun Lee; Min Ho Lee; Dae Sang Lee; Maru Kim; Dae Hyun Jo; Hyosun Park; Hangjoo Cho (Journal of Trauma and Injury)
Purpose We analyzed the characteristics and outcomes of patients with bicycle-related injuries at a regional trauma center in northern Gyeonggi Province as a first step toward the development of improved prevention measures and treatments. Methods The records of 239 patients who were injured in different types of bicycle-related accidents and transported to a single regional trauma center between January 2017 and December 2018 were examined. This retrospective single-center study used data from the Korea Trauma Database. Results In total, 239 patients experienced bicycle-related accidents, most of whom were males (204, 85.4%), and 46.9% of the accidents were on roads for automobiles. Forty patients (16.7%) had an Injury Severity Score (ISS) of 16 or more. There were 125 patients (52.3%) with head/neck/face injuries, 97 patients (40.6%) with injuries to the extremities, 59 patients (24.7%) with chest injuries, and 21 patients (8.8%) with abdominal injuries. Patients who had head/neck/face injuries and an Abbreviated Injury Score (AIS) ≥3 were more likely to experience severe trauma (ISS ≥16). In addition, only 13 of 125 patients (10.4%) with head/neck/face injuries were wearing helmets, and patients with injuries in this region who were not wearing helmets had a 3.9-fold increased odds ratio of severe injury (AIS ≥2). Conclusions We suggest that comprehensive accident prevention measures, including safety training and expansion of safety facilities, should be implemented at the governmental level, and that helmet wearing should be more strictly enforced to prevent injuries to the head, neck, and face.